Autism and Overcoming Job Barriers: Comparing Job-Related Barriers and Possible Solutions in and outside of Autism-Specific Employment - Lorenz, Timo; Frischling, Cora; Cuadros, Raphael; Heinitz, Kathrin (PLOS ONE, 2016)
The aim of this study was to discover how individuals with autism succeed in entering the job market. We therefore sought to identify expected and occurred barriers, keeping them from taking up and staying in employment as well as to identify the solutions used to overcome these barriers. Sixty-six employed individuals with autism–17 of them with autism-specific employment–participated in an online survey. Results showed a variety of possible barriers. Individuals in autism-specific employment named formality problems–problems with organizational and practical process-related aspects of the job entry–most frequently while individuals in non-autism-specific employment mentioned social problems–obstacles concerning communication and human interaction–most. In terms of solutions, both groups used their own resources as much as external help, but differed in their specific strategies. In addition, correlations of an autism-specific employment with general and occupational self-efficacy as well as life and job satisfaction were examined. Possible implications of the results are discussed with regard to problem solving behavior and the use of strengths.